The determinants of occupational pensions - Erik Hernæs; John Piggott; Tao Zhang; Steinar Strøm (University of Oslo, Department of Economics, 2006)
The decision by firms to offer an occupational pension is investigated with a unique linked employer-employee dataset, supplemented with detailed actuarial calculations of the cost to the firms of offering occupational pensions and constructed tax gains from pension contributions versus cash wage, driven by lower tax on wages than on pensions. The tax gains which can be shared between employers and employees by the degree of wage moderation, are clearly associated with the occurrence of an occupational pension plan. An occupational pension is associated with longer average tenure in the firm. Occupational pensions typically are found in large firms, and individual wage negotiations, a high degree of unionization and requirement of long training are all positively associated with an occupational pension. Hence, financial and productivity incentives are found to operate within a moderating institutional framework.
Keywords: C25; D21; G23; 330; Occupational pensions; tax gains; tenure; linked employer-employee datasets; Betriebliche Altersversorgung; Vergütungssystem; Steuerbegünstigung; Norwegen